1998
DOI: 10.1046/j.1365-2133.1998.02062.x
|View full text |Cite
|
Sign up to set email alerts
|

Topical application of α‐tocopherol modulates the antioxidant network and diminishes ultraviolet‐induced oxidative damage in murine skin

Abstract: The aim of this study was to investigate the effects of topical alpha-tocopherol application on epidermal and dermal antioxidants and its ability to prevent ultraviolet (UV)-induced oxidative damage. Hairless mice received topical applications of alpha-tocopherol 24 h before a single, acute UV irradiation (10 x minimal erythemal dose). The four major antioxidant enzymes (catalase, superoxide dismutase, glutathione reductase and glutathione peroxidase), hydrophilic and lipophilic antioxidants, and lipid hydrope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
88
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(99 citation statements)
references
References 63 publications
(101 reference statements)
1
88
1
9
Order By: Relevance
“…The main advantage of the topical administration when compared to the oral administration to treat and prevent skin conditions is the direct delivery of bioactive substances to the target area, thus eliminating concerns about systemic circulation Page 2 / 10 (Meinke et al, 2010;Palombo et al, 2007). The cutaneous delivery of antioxidants is a complementary and well known treatment to prevent skin aging and to avoid dermal diseases, such as skin cancer (Sander et al, 2004;Pinnell, 2003;Dreher et al, 1998;Lopez-Torres et al, 1998). Pinnell (2003) explains that antioxidants are an important alternative to protect the skin from photodamage, and should be associated with sunscreens.…”
Section: Introductionmentioning
confidence: 99%
“…The main advantage of the topical administration when compared to the oral administration to treat and prevent skin conditions is the direct delivery of bioactive substances to the target area, thus eliminating concerns about systemic circulation Page 2 / 10 (Meinke et al, 2010;Palombo et al, 2007). The cutaneous delivery of antioxidants is a complementary and well known treatment to prevent skin aging and to avoid dermal diseases, such as skin cancer (Sander et al, 2004;Pinnell, 2003;Dreher et al, 1998;Lopez-Torres et al, 1998). Pinnell (2003) explains that antioxidants are an important alternative to protect the skin from photodamage, and should be associated with sunscreens.…”
Section: Introductionmentioning
confidence: 99%
“…These effects are mediated in part by UV induced oxidative stress through ROS production (20) cou pled to the impairment of tissue antioxidant defense systems (21). Several studies have indicated that topical applications of antioxidants like a-tocopherols have photoprotective effects on the epidermis in different models of UV photodamage, protecting cutaneous tissues from oxidative damage induced by UV irradiation in vivo (22)(23). The high level of 8iso-PGF2a found in UV irradiated skin and in BCC could also have an intrinsic biologic acti vity 8iso-PGF2 is a well-known mitogen for endothelial cell (24) neutrophil adhesion (25) and cytokine's production (26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…This comprehensive system provides the skin with a protective antioxidant barrier and is well interlinked between its various components [44][45][46]. Most of the system's components were found distributed in skin layers, with higher concentrations in the epidermis than the dermis, correlating with ROS exposure of skin layers [47].…”
Section: Antioxidant Defense Systemmentioning
confidence: 99%